2019
DOI: 10.1002/cbic.201900425
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterization of Isolated Nitrogenase Cofactors from Azotobacter vinelandii

Abstract: The nitrogenase cofactors are structurally and functionally unique in biological chemistry. Despite a substantial amount of spectroscopic characterization of protein‐bound and isolated nitrogenase cofactors, electrochemical characterization of these cofactors and their related species is far from complete. Herein we present voltammetric studies of three isolated nitrogenase cofactor species: the iron–molybdenum cofactor (M‐cluster), iron–vanadium cofactor (V‐cluster), and a homologue to the iron–iron cofactor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…170−172 Interestingly, the subsequent X-ray analysis also suggested that the Fe atoms of the Vcluster were in a more reduced state compared to the M-cluster counterparts. 170 This observation seems to correlate with the measured midpoint potentials of −414 mV and −270 mV versus SHE for the isolated V-and M-clusters, respectively, 139 with the more negative potential relating to a seemingly more reduced Vcluster. Further, the iron−heterometal bonding interactions were found to be weaker for the V-cluster compared to the Mcluster, which would align with the elongated V---Fe distances observed by XAS of the protein, cofactor, and crystallographically characterized V-cluster relative to the Mo-dependent counterpart.…”
Section: Characterization Of V-nitrogenasementioning
confidence: 99%
See 1 more Smart Citation
“…170−172 Interestingly, the subsequent X-ray analysis also suggested that the Fe atoms of the Vcluster were in a more reduced state compared to the M-cluster counterparts. 170 This observation seems to correlate with the measured midpoint potentials of −414 mV and −270 mV versus SHE for the isolated V-and M-clusters, respectively, 139 with the more negative potential relating to a seemingly more reduced Vcluster. Further, the iron−heterometal bonding interactions were found to be weaker for the V-cluster compared to the Mcluster, which would align with the elongated V---Fe distances observed by XAS of the protein, cofactor, and crystallographically characterized V-cluster relative to the Mo-dependent counterpart.…”
Section: Characterization Of V-nitrogenasementioning
confidence: 99%
“…The E m for the one-electron reduced M-cluster, M R , has also been measured to be −465 mV versus NHE, but this could only be obtained in the presence of NifH. Interestingly, the isolated M-cluster has a much more negative potential than when bound to the protein, with reported values for the M OX /M N couple between −320 and −270 mV versus SHE. For a more specific example, the isolated M-cluster in the solvent N -methylformamide (NMF) was found to have potentials for the M OX /M N and M N /M R redox events at −320 mV and −1.00 V versus NHE, respectively. The dramatic change observed in the reduction potentials for the M-cluster bound to and free from the nitrogenase protein demonstrates that the protein environment plays a significant role in tuning the properties of the M-cluster.…”
Section: Structure and Properties Of Nitrogenase Proteinsmentioning
confidence: 99%
“…[69] The redox polymer P(GMA-MMA-PEGMA)-NR has a more negative redox potential (À 0.58 V vs. SCE) than Fe protein (À 0.48 V vs. SCE) which facilitates favorable electron transfer from the redox pendant to the MoFe protein, leading to the generation of 201 � 16 nmol NH 3 À 1 nmol MoFe À 1 h À 1 . Encouraged by the activity of isolated MoFe-proteins, research efforts have been devoted to the investigation of redox properties of nitrogenase enzymes and their isolated cofactors [100] and via DET to the isolated enzyme. [67,101] One of the major limiting factors in mediated biolectrocatalytic N 2 fixation remains the stability of the bioelectrodes in immobilized systems.…”
Section: Bioelectrocatalytic N 2 Fixationmentioning
confidence: 99%
“…Interestingly, a square wave voltammetry study of Av NifDK, which was immobilized on a pyrene-modified hydrogel film and directly attached to the electrode, led to the assignment of −590 mV vs NHE to the M N /M R redox couple, a potential much more negative than that determined indirectly with redox mediators for the same protein in the presence of its reductase partner, Av NifH . Similarly, it was observed that upon extraction of the M-cluster as an intact entity into an organic solvent (e.g., NMF and DMF), the midpoint potentials of the cofactor became more negative, with values of −320 to −270 mV vs SHE and −1 V vs SHE, respectively, reported for the M OX /M N and M N /M R redox couples. Moreover, the change in the potential of the extracted cofactor was shown to be accompanied by a broadening of the cofactor-specific S = 3/2 EPR signal ( g = 4.7, 3.5, 2.0) (Figure B). , Apparently, immobilization of NifDK without NifH on an electrode, or extraction of the cofactor from NifDK into solvents, renders the electronic and redox properties of the M-cluster different than those of its counterpart in the complete nitrogenase system. Nevertheless, both the isolated NifDK protein and the extracted M-cluster are capable of C 1 substrate reduction on their own (see section below), highlighting the catalytic versatility of the various components of nitrogenase.…”
Section: Nitrogenase Enzymes and Their Associated Metalloclustersmentioning
confidence: 99%